Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1074/jbc.m111.251140
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Glycosaminoglycans Are Required for Specific and Sensitive Fibroblast Growth Factor (FGF) 19 Signaling via FGF Receptor 4 and betaKlotho

Abstract: Secreted from intestine, human fibroblast growth factor 19 (hFGF19) is an endocrine metabolic regulator that controls bile acid synthesis in the liver. Earlier studies have suggested that hFGF19 at 10 -100 nM levels signals through FGF receptor 4 (FGFR4) in the presence of a co-receptor, betaKlotho, but its activity and receptor specificity at physiological concentrations (picomolar levels) remain unclear. Here we report that hFGF19 at picomolar levels require sulfated glycosaminoglycans (sGAGs), such as hepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 32 publications
4
29
0
Order By: Relevance
“…This study suggested that the increase in the blood hFGF19 concentrations not only relies on hFGFR4 and hKLB, but also on sGAGs (16). The composition ratio of these highly sulfated structures, including hepatic sGAGs, despite its lower concentration compared to that of HP, shows the same level of activity with HP.…”
Section: Concluding Remarkingsupporting
confidence: 48%
“…This study suggested that the increase in the blood hFGF19 concentrations not only relies on hFGFR4 and hKLB, but also on sGAGs (16). The composition ratio of these highly sulfated structures, including hepatic sGAGs, despite its lower concentration compared to that of HP, shows the same level of activity with HP.…”
Section: Concluding Remarkingsupporting
confidence: 48%
“…It is therefore interesting to postulate that FGF21 regulation of cellular fatty acid metabolism is due to formation of a less potent 1:2 complex of KLB-FGFR1c (31). Future studies will also need to determine the aggregation state of HSPGs to determine their role in the FGF21 signaling complex (31).…”
Section: Discussionmentioning
confidence: 99%
“…Other growth factors require participation of noncovalently bound carbohydrate molecules to activate their receptor. For example, members of the fibroblast growth factor (FGF) family require heparan sulfate proteoglycan to interact productively with their receptors (Nakamura, Uehara et al 2011). …”
Section: Introductionmentioning
confidence: 99%